Nutritional practices of elite swimmers during an intensified training camp: with particular reference to antioxidants - Slattery, K. M.; Coutts, A. J.; Wallace, L. K. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM: Athletes should match their energy intake with expenditure in order to maintain lean body mass. It is also important to consume adequate amounts of antioxidant vitamins and minerals to maintain health. METHODS: To assess the dietary habits of six nationally ranked Australian swimmers physical training load and dietary intake (24 h food recall) and were recorded on a daily basis during a 4 day intensive physical training period. RESULTS: The results showed no significant difference between energy intake and expenditure (P=0.58) or the amount of carbohydrate consumed (P=0.14) compared to the Australian recommended daily intake (RDI). Athletes reported a significantly greater intake of vitamin A (P<0.01), vitamin C (P<0.01), vitamin E (P<0.01) and protein (P<0.01) than the RDI. CONCLUSION: It was concluded that these elite swimmers have an adequate dietary intake to allow for optimal physical training and performance.